(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Introduction: Abnormal liver function in patients with PET and eclampsia affect both maternal and fetal outcome negatively. This study was done to see change of liver function in comparison to normal pregnancy and normal reference value. Methods: Consecutive 47 patients of PET and eclampsia were taken as cases and 35 normal expectant mother were enrolled as controls. ALT, AST, alkaline phosphatase, serum bilirubin, serum creatinine and urine for albumin of patients andnormal pregnant women were tested and compared. Results: ALT, AST, S. Bilirubin, Alkaline phoshatase levels were elevated with more proteinuria among patients with PET and eclampsia, but ALT and alkaline phosphatase levels and level of proteinuria were significantly higher. Conclusions: Liver function impairment is very common in pre-eclampsia and eclampsia. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 9-10